Development of drug discovery screening system by molecular interaction kinetics–mass spectrometry. (25th March 2018) - Obi, Naoko; Fukuda, Tetsuya; Nakayama, Noboru; Ervin, John; Bando, Yasuhiko; Nishimura, Toshihide; Nagatoishi, Satoru; Tsumoto, Kouhei; Kawamura, Takeshi
Abstract : Rationale: Drug discovery studies invariably require qualitative and quantitative analyses of target compounds at every stage of drug discovery. We have developed a system combining molecular interaction analysis and mass spectrometry (LC‐MS) using the principle of nanopore optical interferometry (nPOI) called molecular interaction kinetics–mass spectrometry (MIK‐MS). Since nPOI has high binding capacity, the bond‐dissociated compound can be directly detected using LC‐MS. In this study, we use carbonic anhydrase II (CAII) as a ligand and apply six small compounds as analytes and report the affinity analysis using MIK‐MS. Methods: CAII was immobilized onto a COOH sensor chip using standard amine coupling. A reference surface was prepared by activating and subsequently blocking the surface under identical conditions. An amount of 50 μL of mix solution was injected over the reference channel and sample channel for CAII immobilization. The solutions eluting from the sensor chip were collected from the waste‐line of the SKi Pro system every 30 s. Reconstructed elution samples were then injected into the LC‐MS/MS system. Results: A mixture containing furosemide, acetazolamide, 4‐sulfamoylbenzoic acid, 5‐(dimethylamino)‐1‐naphthalene sulfonamide (DNSA), sulfanilamide and sulpiride (15 μM each) was injected into the CAII‐immobilized sensor chip, and the fractions eluted from the SKi Pro system were collected and subjected to selected reaction monitoring LC‐MS characterization. Specific results were obtained for acetazolamide, DNSA, furosemide and sulpiride. The results suggest that the association–dissociation curve of a mixed sample can be obtained by one‐time MIK‐MS analysis. Conclusions: Six small‐molecule binders of CAII were analyzed quantitatively using nPOI and MIK‐MS, and the results were compared to published surface plasmon resonance (SPR) results. The nPOI and SPR results show good agreement, confirming the reliability of the analysis. Time‐dependent binding results may be obtained by our MS sensorgram approach. Drugs that meet medical needs in a short period are required; this nPOI‐LC‐MS system is considered an important tool for rapid drug discovery.